2014
DOI: 10.1016/j.jsps.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, attitudes and practices toward research among senior medical students

Abstract: We aimed to explore perceptions, attitudes and practices toward research among medical students. A self-administered questionnaire was distributed among senior medical students at the King Saud University, Riyadh, Saudi Arabia. Hundred and seventy two students participated in the study, with 97 males (65.5%). The majority of the students agreed that research is important in the medical field (97.1%, 167/172). A total of 67.4% (116/172) believed that conducting research should be mandatory for all medical stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
162
5
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(194 citation statements)
references
References 15 publications
25
162
5
2
Order By: Relevance
“…This finding is comparable with that of findings of Khan H et al 6 , Forester JP et al 10 , Siemens DR et al 11 , Al Ghamdi KM et al 12 , and Amin TT et al 15 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is comparable with that of findings of Khan H et al 6 , Forester JP et al 10 , Siemens DR et al 11 , Al Ghamdi KM et al 12 , and Amin TT et al 15 .…”
Section: Discussionsupporting
confidence: 91%
“…Regarding barriers for research, majority of students 265 (62.6%) were not having extra time for research followed by lack of guidance 91 (21.5%) and inadequate facilities for research 29 (6.9%).These findings are in agreement with Siemens DR et al 11 , AlGhamdi KM et al 12 , Harsha Kumar HN et al 13 , Mosafa SR et al 14 , Amin TT et al 15 , and Sekhar DS et al 17 .…”
Section: Discussionsupporting
confidence: 68%
“…This was in accordance with the study conducted by Giri et al, 11 AlGhamdi et al, 14 and Pawar et al 9 Another study conducted by Sharma et al 13 revealed contrasted results due to inadequate financial facilities for research.…”
Section: Discussionsupporting
confidence: 90%
“…[11][12][13][14][15][16][17][18][19] Studies on chiropractic students' attitudes specifically have also been done. For example, Newell and Cunliffe 19 conducted such a study on undergraduate students at McTimoney Chiropractic College and found that 64% of their 119 student respondents found research interesting, 54% thought it was difficult, and 75% considered chiropractic research to be necessary.…”
Section: Discussionmentioning
confidence: 99%